CELEBRITY VIDEO INTERVIEWS: COMMUNICATIVE FAILURES OF JOURNALISTS IN UKRAINIAN AND GERMAN LINGUISTIC CULTURES - Khrystyna Yu. Dyakiv (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
Background: The Internet and television offer numerous popular video interviews with celebrities and prominent personalities in the sphere of culture, therefore they are the most frequent ones on the YouTube video hosting and they receive the largest number of views in both linguistic cultures under study. However, to date, there is no coherent picture of the communicative failures in them, especially in the contrasting aspect on the basis of the Ukrainian and German languages. Purpose: The purpose of the article is to investigate the communicative failures of journalists in celebrity video interviews in the Ukrainian and German linguistic cultures from the point of view of social interaction and the theory of speech genres, establishing common and distinctive features in both linguistic cultures. The problems of typology of communicative failures in celebrity video interviews in Ukrainian and German are examined. The subject matter, genre and language specificity of celebrity video interviews are defined, as well as the reasons of communicative failures in them, taking into account the perspectives of the interviewer, as well as structural levels of the genre (the level of external structure, of internal structure, and situational level of realization). Results: The analysis of celebrity video interviews conducted in the article has shown that communicative failures are present at all levels of the genre in both languages. The analysis made it possible to conclude that behind a communicative failure there is a violation caused by a journalist. Communicative failures in the Ukrainian and German linguistic cultures have more in common than not. However, in the Ukrainian linguistic culture, there are more language mistakes and failures from the position of the interviewer, and communicative failures are more frequent. Common in both linguistic cultures are such failures: on the extrastructural level (lack of communica- level (lack of communicative competence, strategic and intentionally communicative failure), on the intrastructural level (phonetic and syntactic) and at the intermediate level (‘fatal’ introductory and further questions). The Ukrainian interviews are characterized by low quality of journalistic training in general, inconvenient time and place of interviewing (on the extrastructural level), lexical and grammatical failures (on the intrastructural level), as well as lack of metacommunication and accumulation of multi-dimensional questions (on the intermediate level). The German interviews are characterized by excessive hard talks from the standpoint of journalists on the extrastructural level.